Studies of Some Lanthanide(III) Nitrate Complexes of Schiff Base Ligands - Kishor Arora Mukesh Sharma; Mukesh Sharma; K. P. Sharma (E-Journal of Chemistry)
The studies of 16 new lanthanide(III) nitrate complexes of Schiff base ligands are discussed. Schiff bases were obtained by the condensation of 2–methyl–4–N,N–bis–2' –cyanoethyl aminobenzaldehyde with aniline and 3 different substituted anilines. Lanthanide(III) nitrates, viz. gadolinium(III) nitrate, lanthanum(III) nitrate, samarium(III) nitrate and cerium(III) nitrate were chosen to synthesize new complexes. The complexes were characterized on the basis of physicochemical studies viz. elemental analysis, spectral, viz. IR and electronic spectral and magnetic studies. TGA studies of some of the representative complexes were also done. Some of the representative complexes were also screened for the anti microbial studies.